2022
DOI: 10.3389/fpubh.2022.871934
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Conditions Among E-Learning Students During the COVID-19 Pandemic

Abstract: AimThe COVID-19 pandemic has forced the education system to undergo changes, which have also affected universities. E-learning became the main form of education, reducing interpersonal contacts, which could affect the mental wellbeing of students. The aim of this study was to investigate the prevalence of depressive symptoms and the level of perceived stress during e-learning among Polish students and to identify the factors for predicting higher levels of depression symptoms.MethodsThe study included 753 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Learning from home is a significant obstacle to making new friends, maintaining existing relationships, and creating and carrying out new or existing initiatives. Studies have shown that students studying remotely via e-learning during the COVID-19 pandemic experienced high levels of stress and depressive symptoms [82]. Also, the percentage of students who reported suicidal thoughts at the time is alarming.…”
Section: Psychological and Social Aspects Of The Pandemic And Mental ...mentioning
confidence: 99%
“…Learning from home is a significant obstacle to making new friends, maintaining existing relationships, and creating and carrying out new or existing initiatives. Studies have shown that students studying remotely via e-learning during the COVID-19 pandemic experienced high levels of stress and depressive symptoms [82]. Also, the percentage of students who reported suicidal thoughts at the time is alarming.…”
Section: Psychological and Social Aspects Of The Pandemic And Mental ...mentioning
confidence: 99%
“…Likewise, there are concerns regarding the adverse effects of COVID-19 on mental distress, sleep disturbances, lowered mood, sadness, tearfulness, and impaired concentration [ 21 ]. Furthermore, it has been reported that psychological reactions to the COVID-19 pandemic can range from panic behaviour or collective hysteria, through feelings of hopelessness and despair, to suicidal behaviour [ 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term effects of the pandemic on students’ mental health are unknown but numerous studies report increased stress levels, depression, anxiety, insomnia, eating disorders, and suicidal thoughts and behaviors [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The prevalence of depression among students before the pandemic had settled at 30% but [ 8 ], based on the results from studies conducted in many countries, a significant increase in depressive symptoms can currently be observed: Spain, 31.19% ( n = 2530); Lebanon, 33.4% ( n = 520); Slovakia, 47% ( n = 3051); the USA, 48.14% ( n = 2031); China, 48.3 ( n = 4872); France, 49.5% ( n = 69,054); Poland, 56.4% ( n = 753); and Greece, 60.9% ( n = 1000) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Scientists highlight that the strongest predictor of depression is elevated stress [ 18 , 19 ], while depression increases the risk of suicidal thoughts and suicide [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists highlight that the strongest predictor of depression is elevated stress [ 18 , 19 ], while depression increases the risk of suicidal thoughts and suicide [ 20 , 21 ]. Moreover, e-learning has been shown to be a predictor of increased levels of stress and depression among students due to demonstrated limited social contact, decreased motivation to learn, negative impact on knowledge and fear of lower grades [ 16 ]. Time spent in front of a computer or phone screen has increased significantly as a result of distance learning and contact with colleagues through communicators, which predict a higher risk of anxiety and depression [ 22 ].…”
Section: Introductionmentioning
confidence: 99%